Combined indicator assists in early recognition of retinopathy of prematurity - Wen Shi; Liping Zhu; Xiaori He; Shuo Wang; Cheng Wang (Scientific Reports)
Abstract This research aimed to investigate the value of clinical data in preterm infants on admission for the early prediction of retinopathy of prematurity (ROP). 98 preterm infants (66 males and 32 females) with an average gestational age of 30.42 ± 1.20 weeks were included. Basic vital signs, clinical tests, and maternal information were collected at admission. Preterm infants were divided into a non-ROP group and a ROP group based on whether they eventually developed ROP. The receiver operating characteristic (ROC) curve was used to evaluate the predictive value of the above indexes and the combined indexes in the ROP of preterm infants. (1) The differences in systolic blood pressure (SBP), red blood cell count (RBC), hemoglobin (HGB), direct bilirubin (DBIL), and total bilirubin (TBIL) were statistically significant between the non-ROP group and ROP group (all P < 0.05). (2) RBC, HGB, DBIL, and TBIL, all of which have diagnostic value for ROP [area under curve (AUC) 0.643, 0644, 0.887, and 0.744, respectively, all P < 0.05]. (3) The combined indicator possessed a good diagnostic value for ROP (AUC of 0.962, P < 0.05), with a sensitivity and specificity of 88.64% and 91.49%, respectively. (4) Combined indicator (body temperature, body weight, heart rate, SBP, diastolic blood pressure, mean arterial pressure, RBC, HGB, red blood cell distribution width, DBIL, TBIL) has better diagnostic value for ROP than each of RBC, HGB, DBIL, and TBIL alone (Z-value 5.386, 5.475, 2.410 and 4.420, respectively, all P < 0.05). Combined indicator has good predictive value for ROP in preterm infants.